Microbiological Quality Analysis of Drinking Water in An-Nuriyah Islamic Boarding School Wonocolo Surabaya - Wikurendra, Edza; Wijaya, Satriya; Nagy, Imre (Journal of Global Research in Public Health, 2020)
The need for water in an area will always increase with population growth, while the water itself decreases in terms of quality, quantity, and continuity. The potential for health problems due to the microbiological quality of drinking water that does not meet the requirements is very high. This study aimed to analyze the microbial quality of drinking water in An-Nuriyah Islamic Boarding School Wonocolo Surabaya. This research is a descriptive study with a cross-sectional approach. This research sample is drinking water consumed by the student in An-Nuriyah Islamic Boarding School Wonocolo Surabaya, which comes from three sources: refill drinking water, boiled water, and bottled drinking water. This study showed that the Escherichia coli parameters' microbiological quality in the three drinking water sources resulted in 0/100 ml samples. Each head was obtained for the Coliform parameters. Namely, 125/100 ml refill drinking water, 2/100 ml bottled drinking water, and 100/100 ml boiled water samples. The results of this study conclude that the microbiological quality of drinking water at An-Nuriyah Islamic Boarding School Wonocolo Surabaya meets the requirements of Minister of Health Regulation Number 492/MENKES/Per/IV/2010 for Escherichia coli parameters, while Coliform parameters do not meet the criteria of Minister of Health Regulation Number 492/MENKES/Per/IV/2010.